PERCEPTION OF THE NATIONAL ENTREPRENEURSHIP CONDITIONS – DIFFERENCES ACROSS TIME AND EXPERT SPECIALIZATION (The South East European Journal of Economics and Business, 2021)
Creating an external context that will have nourishing effect on the entrepreneurial activities seems to be timely, path and location dependent process. The systemic explorations of the national entrepreneurial context (environment) are still relatively underrepresented. The paper explores strengths and weaknesses of the national entrepreneurship conditions in Croatia and how stable these conditions are in the longer time frame. The aim of the study is to provide more detailed insight on the differences in perceptions among experts engaged in Global Entrepreneurship Monitor (GEM) and along the time. Findings indicate deterioration of the national entrepreneurial conditions in Croatia. Experts’ perceptions of national entrepreneurial conditions diverge between experts who have and those who do not have prior entrepreneurial experiences. The time also matters – perceptual difference in evaluating the quality of national entrepreneurship conditions is observed across 2015-2018.